Fatty Acids and Cardiometabolic Health - Wu, Jason (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The impact of fat intake on hypercholesterolemia and related atherosclerotic cardiovascular diseases has been studied for decades. However, the current evidence base suggests that fatty acids also influences cardiometabolic diseases through other mechanisms including effects on glucose metabolism, body fat distribution, blood pressure, inflammation, and heart rate. Furthermore, studies evaluating single fatty acids have challenged the simplistic view of shared health effects within fatty acid groups categorized by degree of saturation. In addition, investigations of endogenous fatty acid metabolism, including genetic studies of fatty acid metabolizing enzymes, and the identification of novel metabolically derived fatty acids have further increased the complexity of fatty acids' health impacts. This Special Issue aims to include original research and up-to-date reviews on genetic and dietary modulation of fatty acids, and the role and function of dietary and metabolically derived fatty acids in cardiometabolic health.